Rapid review of multisystem inflammatory syndrome in paediatrics: What we know one year later - Megan Striha (Public Health Agency of Canada, 2021)
Background: Multisystem inflammatory syndrome in children (MIS-C) associated with coronavirus disease 2019 (COVID-19) is an emerging condition that was first identified in paediatrics at the onset of the COVID-19 pandemic. The condition is also known as pediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus 2 (PIMS-TS or PIMS), and multiple definitions have been established for this condition that share overlapping features with Kawasaki Disease and toxic shock syndrome.